Physical education candidate teachers' beliefs about vocational self-esteem - A. Canpolat; Murat Ozsaker (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to determine epistemological belief and vocational self-esteem physical educationcandidate teachers of Physical Education and Sports Department in 3 different universities, and also to examineeffect of epistemological beliefs on vocational self-esteem. A total of 346 candidate teacher respondents (137 femaleand 209 male) participated in the study. Epistemological Beliefs and Vocational Self-Esteem Scale were used todetermine candidate teachers' epistemological beliefs and vocational self-esteem levels, respectively. Independentsample t test, bivariate correlation, and multiple regression analysis were used to analyze the data. According tothe analyses, there was a negative moderate-level significant relationship between Vocational Self-Esteem and twosubscales of Epistemological Beliefs scale (The Belief That Learning Depends on Effort and the Belief ThatLearning Depends on Ability). However, there was no relationship between vocational self-esteem and the beliefthat there is only one right answer subscale. In addition, The Belief That Learning Depends on Effort and TheBelief That Learning Depends on Ability were the negative and significant predictors of Vocational Self Esteem.